Through a different lens: examining commonality and divergence in constructions and depictions of the sexuality of persons with physical disabilities in South Africa - Hunt, Xanthe (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.